EXPERIENTIAL LEARNING AND NATIONAL CURRICULUM GUIDELINES FOR NURSING UNDERGRADUATE COURSES: INTEGRATIVE REVIEW OF THE LITERATURE - Paula Bresolin; Jussara Gue Martini; Daniele Delacanal Lazzari; Isis da Silva Galindo; Jeferson Rodrigues; Maria Helena Pires Araújo Barbosa (Universidade Federal do Paraná, 2019)
the achievement of the general competencies provided for in the National Curriculum Guidelines for Nursing Undergraduate Courses.Method: An integrative review was conducted from January 2013 to August 2017.Results: For the systematization of the discussion of the results, the presentation of the 43 selected articles was based on the general competencies set out in the National Curriculum Guidelines.Conclusion: Experiential learning as a teaching and learning strategy in nursing and its contributions are consistent with the general competencies and skills set out in the National Curriculum Guidelines. The Health Care skill was the most covered skill in all the studies. It is noteworthy that experiential learning is maximized when it reaches critical-reflective thinking in vocational training. The simulation addressed in the selected articles was an effective teaching methodology for nursing students.